Canada's national parks [videorecording (DVD)] - Johnson, Dale (Trailwood Films, 2000)
A guided tour of Canadian Parks from East to West. Starting with L'Anse aux Meadows Park in Newfoundland, where Vikings waded ashore long ago. We explore the forested Parks of central Canada to the stunning mountains of the West. Included are Gros Moren, Cape Breton Highlands, Kejimkujik, Prince Edward Island, Kouchibouquac, Fundy, La Mauricie, Point Pelee, Ellesmere Island, Grasslands, Riding Mountain, Waterton Lakes, Banff, Jasper, Kootenay, Yoho, Wood Buffalo, Nahanni, Pacific Rim and Kluane.